The Social Realities of Undocumented Mexican Immigrant Women and the Broader Implications for Adult Educators - San Juanita Garcia (Adult Education Research Conference, 2011)
This study highlights the critical realities Mexican undocumented immigrant women face in an anti-immigrant environment. Based on thirty face- to-face interviews with unauthorized Mexican immigrant women in Houston, Texas, a traditional gateway city, this study aims to explore the significance and reality that undocumented Mexican immigrant women endure in their everyday lives in an anti-immigrant climate and how this impacts depression symptomatology. I describe detailed narratives of three factors and their association to symptoms of depression among my participants. The findings provide recommendations for future research and implications for adult educators who teach vulnerable populations.
Keywords: Nativism; Mexican Undocumented Immigration; Mental Health